2008
DOI: 10.1007/s00213-008-1291-8
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the latency of action of antidepressants by 17 β-estradiol in the forced swimming test

Abstract: E(2) clearly reduced the latency to the onset of action for these ADs in the FST. These results represent an interesting therapeutic strategy for the treatment of depression in perimenopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 81 publications
2
19
0
Order By: Relevance
“…In accordance with our findings, which showed no effect of repeated testing during the entire experiment, previous studies showed no habituation in FST or OF testing in the rat as well (Estrada-Camarena et al 2008;Gutierrez-Garcia and Contreras 2009). On the contrary, other works demonstrate that repetition of these tests can lead to changes as adaptation to the procedure (Dalla et al 2005, Häidkind et al 2003.…”
Section: Discussionsupporting
confidence: 94%
“…In accordance with our findings, which showed no effect of repeated testing during the entire experiment, previous studies showed no habituation in FST or OF testing in the rat as well (Estrada-Camarena et al 2008;Gutierrez-Garcia and Contreras 2009). On the contrary, other works demonstrate that repetition of these tests can lead to changes as adaptation to the procedure (Dalla et al 2005, Häidkind et al 2003.…”
Section: Discussionsupporting
confidence: 94%
“…Many reports have indicated the possibility that exogenous estrogen administration can cure and/or treat depression using animal models, [11][12][13][14] but clinical findings suggest that hormone replacement therapy causes side effects, for example, a high risk of stroke, venous thromboembolism, and breast cancer. 15) Hence it is necessary to develop a treatment method for depression that takes the place of estrogen without any side effects, for example, ingredients of daily food.…”
Section: Discussionmentioning
confidence: 99%
“…For example, exogenous treatment with estrogen of ovariectomized animals changes monoamine metabolism in the brain. [11][12][13][14] Walf et al reported that estrogen receptor (ER) -specific selective ER modulator (SERM) showed an antidepressant-like effect, but not ER-specific SERM, and concluded that the antidepressant-like effect of estradiol may involve ER in the hippocampus. 14) ER, rather than ER, is dominantly expressed in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…These combination treatments produced antidepressant-like effects in OVX rats (Estrada-Camarena et al 2004; Recamier-Carballo et al 2012) as well as in orchiectomized male rats (Martinez-Mota et al 2008). Similarly, the antidepressant-like effect of chronic DMI in OVX animals was seen earlier in the group treated with a single E2 injection than in animals treated with vehicle (Estrada-Camarena et al 2008). Further, ineffective doses of EB and/or P worked synergistically with sub-optimal doses of DMI to produce anxiolytic-like effects in the shock probe-burying test (Martinez-Mota et al 2000).…”
Section: Discussionmentioning
confidence: 94%